(untitled) (Research, Society and Development, 2021)
The objective was to evaluate the oral health conditions and perceptions of people with visual impairment. This is a cross-sectional, exploratory, quantitative study, carried out with 72 visually impaired people in an institute for the blind in the interior of the state of São Paulo. Were applied the OHIP-14 questionnaires for adults, CPQ-11-14 for children and DMFT index to assess oral health condition. Sociodemographic variables were considered. The data were analyzed in a descriptive way, through relative, absolute and analytical frequencies. Categorical variables were compared using the Chi-square test and Fisher’s exact test, with a 5% significance level. The average DMFT was 12.8 for the average age 34.5 years, 50% were totally blind and 65.3%, male. Most of them reported the need to go to the dentist (66.7%), with statistical significance associated with the perception of oral health (p = 0.024). Among the total blindness and low vision groups, the psychological discomfort dimension was statistically significant (p = 0.0008), demonstrating a greater impact on the quality of life of the total blindness group. It is concluded that individuals with visual impairment have a good perception of their oral health and oral condition compatible with the Brazilian population average. However, specific oral health promotion actions are still needed to meet their needs.